Implantation of a Dual-Chamber Pacemaker in a Patient With Situs Inversus and Dextrocardia Using a Novel Ultrasound Technique - Augusto, JB (2019)
We report a case of a 43-year-old man with situs inversus and dextrocardia who was admitted with syncope in the setting of complete atrioventricular block. The complex anatomy poses a considerable challenge to transvenous permanent pacemaker implantation. We employed a novel technique using vascular ultrasound and agitated saline solution to assist with lead positioning. This technique could be useful in pediatric populations or younger patients, in whom the use of ionizing radiation is an important issue.